Review: Astrocytes in Alzheimer's disease and other age‐associated dementias: a supporting player with a central role. (June 2017) - Garwood, C. J.; Ratcliffe, L. E.; Simpson, J. E.; Heath, P. R.; Ince, P. G.; Wharton, S. B.
Abstract : Astrocytes have essential roles in the central nervous system and are also implicated in the pathogenesis of neurodegenerative disease. Forming non‐overlapping domains, astrocytes are highly complex cells. Immunohistochemistry to a variety of proteins can be used to study astrocytes in tissue, labelling different cellular components and sub‐populations, including glial fibrillary acidic protein, ALDH1L1, CD44, NDRG2 and amino acid transporters, but none of these labels the entire astrocyte population. Increasing heterogeneity is recognized in the astrocyte population, a complexity that is relevant both to their normal function and pathogenic roles. They are involved in neuronal support, as active components of the tripartite synapse and in cell interactions within the neurovascular unit (NVU), where they are essential for blood–brain barrier maintenance and neurovascular coupling. Astrocytes change with age, and their responses may modulate the cellular effects of neurodegenerative pathologies, which alone do not explain all of the variance in statistical models of neurodegenerative dementias. Astrocytes respond to both the neurofibrillary tangles and plaques of Alzheimer's disease, to hyperphosphorylated tau and Aβ, eliciting an effect which may be neuroprotective or deleterious. Not only astrocyte hypertrophy, in the form of gliosis, occurs, but also astrocyte injury and atrophy. Loss of normal astrocyte functions may contribute to reduced support for neurones and dysfunction of the NVU. Understanding how astrocytes contribute to dementia requires an understanding of the underlying heterogeneity of astrocyte populations, and the complexity of their responses to pathology. Enhancing the supportive and neuroprotective components of the astrocyte response has potential translational applications in therapeutic approaches to dementia. Abstract : This review provides a broad overview of the role of astrocytic populations in the healthy brain and their role in ageing and neurodegenerative diseases with an emphasis on Alzheimer's disease. Perturbation of astrocyte function may contribute to the pathogenesis of dementia and may present an additional therapeutic target.